SEBARAN VEGETASI DAN KONSENTRASI GAS CO - Pb DI TAMAN KB, SIMPANG LIMA, DAN TUGU MUDA KOTA SEMARANG - Margahayu, Hilyana; Hariyanto, Hariyanto; Setyowati, Dewi Liesnoor (Indonesian Journal of Conservation, 2015)
The warming temperatures are caused high gas escaping emissions in the air. Industrial activities and transport in the city led to increased gas CO, Pb, dust and noise. It needs the efforts to restructure and improve the environment through a city park. City park in addition to having a value of beauty is also able to absorb dust particles, gases CO, Pb and noise. This study aimed to vegetation distribution and gas concentration CO, Pb, dust, noise in the garden city of Semarang. The object of this study was the city park area in the district of Semarang and Semarang in the form of South Central. The research sample KB Park, Taman Simpang Lima and Garden Tugu Muda. The research variables include the type and amount of vegetation, species composition of vegetation, vegetation density and state of vegetation distribution, gas concentration CO, Pb, dust and noise. Data analysis techniques use quantitative descriptive analysis. The distribution of vegetation in the park KB, Simpang Lima Park and Garden Tugu Muda of aspects of the composition of the vegetation is very little to the value category â¤20,0%, aspects of the category of very rare vegetation density value â¤14,0%, and distribution of vegetation including the category of very ugly with â¤20,0% value. The concentration of air pollutants such as dust 409 Î¼gr / m3 and 76.19 dBA noise both have exceeded the national ambient air quality standard. When compared to the air pollution in Taman Simpang Lima and Garden Tugu Muda higher than Taman KB. Semarang City Government needs to increase the number of trees in the Garden of KB to be effective in lowering the levels of CO, lead and noise.Â Memanasnya suhu di kota-kota besar disebabkan oleh tingginya gas emisi yang lepas di udara. Kegiatan industri dan transportasi di kota menyebabkan meningkatnya gas CO, Pb, debu dan kebisingan. Diperlukan usaha untuk menata dan memperbaiki lingkungan melalui taman kota. Taman kota selain mempunyai nilai keindahan juga mampu menyerap partikel debu, gas CO, Pb dan kebisingan. Tujuan penelitian mengetahui sebaran vegetasi dan konsentrasi gas CO, Pb, debu, kebisingan di taman Kota Semarang. Objek penelitian ini adalah kawasan taman kota di Kecamatan Semarang berupa Selatan dan Semarang Tengah. Sampel penelitian Taman KB, Taman Simpang Lima dan Taman Tugu Muda. Variabel penelitian meliputi jenis dan jumlah vegetasi, komposisi jenis vegetasi, kerapatan vegetasi dan keadaan sebaran vegetasi, konsentrasi gas CO, Pb, debu dan kebisingan. Teknik analisis data berupa analisis deskriptif kuantitatif. Sebaran vegetasi di Taman KB, Taman Simpang Lima dan Taman Tugu Muda dari aspek komposisi vegetasi kategori sangat sedikit dengan nilai â¤20,0%, aspek kerapatan vegetasi kategori sangat jarang dengan nilai â¤14,0%, dan sebaran vegetasi termasuk kategori sangat jelek dengan nilai â¤20,0%. Konsentrasi cemaran udara seperti debu 409 Âµgr/m3 dan kebisingan 76,19 dBA keduanya telah melebihi batas baku mutu udara ambien nasional. Kalau dibandingkan maka cemaran udara di Taman Simpang Lima dan Taman Tugu Muda lebih tinggi dari Taman KB. Pemkot Kota Semarang perlu menambah jumlah pohon di Taman KB agar efektif dalam menurunkan kadar CO, timbal dan kebisingan.Â